How Married Couples Cope with Sexual Behavior Changes During Pregnancy - Nafisah, Lu'lu; Pascariyanti, Tifa (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2019)
Background: Sexual health plays an important role for the quality of life. Most partners are sexually active both before and during pregnancy but they are concerned about their sexual activities that affect the fetus or pregnancy. Method: This study was conducted to explore sexual behavior changes during pregnancy and to identify factors related its changes. This study used systematic review based on the PRISMA Protocol. The literature search was conducted from April 14th to April 17th, 2017 by electronic databases such as Proquest, Scopus, JSTOR and Google Scholar using relevant keywords. The initial screening was conducted by reading the titles and abstracts. The relevant studies were further selected using inclusion and exclusion criteria. Result: Ten studies included in this review. Two studies were conducted by a qualitative approach, eight studies by cross-sectional, and two studies by cohort. Sexual intercourse frequency, coitus positions, desire, and orgasm was changed during the gestational stage due to parents’ fear of adverse effects, socio-cultural factors and maternal conditions. Conclusions: Factors associated to sexual behavior changes were maternal age, knowledge, marital status, level of education, perception, socio-cultural factors, religious factor, access to information, and social support.